KONTRIBUSI USAHATANI JAGUNG MANIS TERHADAP PENDAPATAN KELUARGA DI DESA KALASEY KECAMATAN MANDOLANG KABUPATEN MINAHASA PROVINSI SULAWESI UTARA (Studi Kasus : Petani Jagung Manis di Desa Kalasey) - Angel Trifina Zakaria; Elsje Pauline Manginsela; Benu Olfie Liesje Susana (AGRI-SOSIOEKONOMI, 2020)
This study aims to determine how much the contribution of sweet corn farming to family income and the amount of contribution included in what category. The research location was in Kalasey Village, Mandolang District, Minahasa Regency, North Sulawesi Province. Data collection was conducted from March to May 2019. Sampling was carried out in a population of 12 sweet corn farmers. This research uses primary and secondary data. Primary data were collected through direct interviews with sweet corn farmers. Secondary data were obtained from the Kalasey Village Office. Data analysis uses the contribution contribution formula. The results showed that the level of contribution of sweet corn farming was 22.02% which was classified in the medium category.